2021
DOI: 10.1038/s41420-021-00747-y
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-scale CRISPR-Cas9 knockout screening in hepatocellular carcinoma with lenvatinib resistance

Abstract: Lenvatinib is the first target drug approved for advanced hepatocellular carcinoma (HCC). However, the development of drug resistance is common, and the mechanisms of lenvatinib resistance and resistant targets in HCC are poorly understood. By using CRISPR/Cas9 library screening, we screened out two key resistance genes, neurofibromin 1(NF1), and dual specificity phosphatase 9 (DUSP9), as critical drivers for lenvatinib resistance in HCC. With RNAi knockdown and CRISPR/Cas9 knockout models, we further clarifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 33 publications
(36 reference statements)
0
55
0
Order By: Relevance
“…However, it still cannot prevent patients from developing drug resistance, resulting in a poor prognosis [24] .…”
Section: Introductionmentioning
confidence: 99%
“…However, it still cannot prevent patients from developing drug resistance, resulting in a poor prognosis [24] .…”
Section: Introductionmentioning
confidence: 99%
“…Xue Sui et al identi ed a novel cisplatin-resistant esophageal oncogene, ERCC8, based on genome-scale CRISPR/Cas9 screening [21]. In Lu Yonggang's study, they performed a genome-wide CRISPR/Cas9 knockout library screen using the HCC cell line Huh7 [22]. They identi ed two key resistance genes, neuro brin 1 (NF1) and bi-speci c phosphatase 9 (DUSP9), and demonstrated that they induce Lenvatinib resistance by activating PI3K/AKT and MEK/ERK signaling pathways in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…They identi ed two key resistance genes, neuro brin 1 (NF1) and bi-speci c phosphatase 9 (DUSP9), and demonstrated that they induce Lenvatinib resistance by activating PI3K/AKT and MEK/ERK signaling pathways in vivo and in vitro. They also screened out trametinib, a small-molecule pathway inhibitor that can be used to reverse Lenvatinib resistance in HCC [22]. Shanzhou Huang et al identi ed six genes associated with Lenvatinib resistance in HCC HepG2 and Huh7 cell lines, including DUSP4, CCBL1, DHDH, CNTN2, NOS3 and TNF.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using CRISPR/Cas9 library screening method, two key resistance genes, neurofibromin 1(NF1) and dual specificity phosphatase 9 (DUSP9), are screened out as critical drivers for Lenvatinib resistance in HCC cells. Trametinib, an inhibitor of MEK pathway, can be used to reverse Lenvatinib resistance mediated by NF1 and DUSP9 loss in HCC cells ( Lu et al, 2021 ). These findings suggest that targeting the resistance-associated molecules or pathway will improve the anti-tumor effect of Lenvatinib therapy for HCC.…”
Section: Discussionmentioning
confidence: 99%